CRISPR memories in single cells - Anke Sparmann; Chase L Beisel (Molecular Systems Biology)
Abstract CRISPR‐Cas systems allow bacteria to memorize prior infections as a means to combat the same invader if it attempts another attack in the future. While the underlying mechanisms of this bacterial immunity have been intensely studied over the past decade, little attention has been paid to CRISPR defense at the single‐cell level. In their recent work, Brouns and colleagues (McKenzie et al, 2022) track memory acquisition and defense in individual cells and find a wide range of temporal dynamics that shape how a cell population experiences and combats an active infection.